Nupr1/Chop signal axis is involved in mitochondrion-related endothelial cell apoptosis induced by methamphetamine - Cai, D.; Huang, E.; Luo, B.; Yang, Y.; Zhang, F.; Liu, C.; Lin, Zhoumeng; Xie, W. B.; Wang, H. (My University, 2016)
Methamphetamine (METH) abuse has been a serious global public health problem for decades. Previous studies have shown that METH causes detrimental effects on the nervous and cardiovascular systems. METH-induced cardiovascular toxicity has been, in part, attributed to its destructive effect on vascular endothelial cells. However, the underlying mechanism of METH-caused endothelium disruption has not been investigated systematically. In this study, we identified a novel pathway involved in endothelial cell apoptosis induced by METH. We demonstrated that exposure to METH caused mitochondrial apoptosis in human umbilical vein endothelial cells and rat cardiac microvascular endothelial cells in vitro as well as in rat cardiac endothelial cells in vivo. We found that METH mediated endothelial cell apoptosis through Nupr1-Chop/P53-PUMA/Beclin1 signaling pathway. Specifically, METH exposure increased the expression of Nupr1, Chop, P53 and PUMA. Elevated p53 expression raised up PUMA expression, which initiated mitochondrial apoptosis by downregulating antiapoptotic Bcl-2, followed by upregulation of proapoptotic Bax, resulting in translocation of cytochrome c (cyto c), an apoptogenic factor, from the mitochondria to cytoplasm and activation of caspase-dependent pathways. Interestingly, increased Beclin1, upregulated by Chop, formed a ternary complex with Bcl-2, thereby decreasing the dissociative Bcl-2. As a result, the ratio of dissociative Bcl-2 to Bax was also significantly decreased, which led to translocation of cyto c and initiated more drastic apoptosis. These findings were supported by data showing METH-induced apoptosis was significantly inhibited by silencing Nupr1, Chop or P53, or by PUMA or Beclin1 knockdown. Based on the present data, a novel mechanistic model of METH-induced endothelial cell toxicity is proposed. Collectively, these results highlight that the Nupr1-Chop/P53-PUMA/Beclin1 pathway is essential for mitochondrion-related METH-induced endothelial cell apoptosis and may be a potential therapeutic target for METH-caused cardiovascular toxicity. Future studies using knockout animal models are warranted to substantiate the present findings.
Citation: Cai, D., Huang, E., Luo, B., Yang, Y., Zhang, F., Liu, C., . . . Wang, H. (2016). Nupr1/Chop signal axis is involved in mitochondrion-related endothelial cell apoptosis induced by methamphetamine. Cell Death & Disease, 7, 14. http://doi.org/10.1038/cddis.2016.67
Keywords: Endoplasmic-Reticulum Stress; Dopaminergic Neuron Apoptosis; Blood-Brain-Barrier; Jnk/C-Jun Pathway; Bh3-Only Proteins; Death